Potential of eggshells as low cost adsorbent for the removal of methylene blue dye - Khor, Hui Min (2016)
This study presents the application of response surface methodology (RSM) to study the effects of process parameters on the removal percentage of Methylene Blue dye using eggshell powders as low cost adsorbent. A two level three factor (2³) full factorial Central Composite Design (CCD) by Design Expert Version 9.0 was employed for experimental designs, process modeling and optimisation study. Three process parameters were adsorbent dosage (0.2-2.0 g), contact time (5-60 min) and initial dye concentration (10-50 mg/L). Based on CCD, a quadratic model was developed for the removal of MB dye. The signiﬁcance of the model and correlation coefficient were tested by the analysis of variance (ANOVA), actual versus predicted and normal probability plots. The model obtained was significant at 95% confidence level. Results showed that the predicted model was found to be in agreement with experimental data. Correlation coefficient, R² obtained for the model is 0.808. The responses of MB dye removal percentage by using eggshell powders were significantly influenced by linear effect of adsorbent dosage, quadratic effect of time, the interaction effects between adsorbent dosage with initial dye concentration and the interaction effect between times with initial dye concentration. The optimum adsorbent dosage, contact time and initial dye concentration for removal percentage of MB dye were found to be 2.0 g, 32.5 min and 30 mg/L. Removal percentage for MB dyes (89.3%) was obtained under the optimal conditions.